Pemetaan Kawasan Wilayah Rawan Banjir di Kelurahan Mugirejo, Kota Samarinda - Aria Nugraha, Difa; Pratiwi Ashta , Dwinsani; Kharisma Kadri, Mohtana; Ariyaningsih , Ariyaningsih (COMPACT: Spatial Development Journal, 2024)
Flooding is a common problem in Mugirejo Subdistrict, Samarinda City. The floods are caused by illegal mining activities in the area, making Mugirejo Subdistrict part of a high flood disaster class with a potential flood hazard area of 582 hectares, representing 18.34% of the flood-prone area in Sungai Pinang District. This study aims to map flood-prone areas in Mugirejo Subdistrict using secondary data collection methods, which involve quantitative data such as the basic physical SHP data of Mugirejo Subdistrict. This data is then analyzed using spatial analysis with the overlay method from the basic physical data. The data will be used to create a map of flood-prone areas and to assess the impact on population aspects, public facilities, road and drainage infrastructure, as well as disaster management in Mugirejo Subdistrict, with results indicating that 1149.71 hectares are flood-prone areas.